Health financing for the poor produces promising short-term effects on utilization and out-of-pocket expenditure: evidence from Vietnam - Minh Pham; Bales Sarah; Axelson Henrik; Ekman Björn; Gerdtham Ulf-G (BMC, 2009)
Abstract Background Vietnam introduced the Health Care Fund for the Poor in 2002 to increase access to health care and reduce the financial burden of health expenditure faced by the poor and ethnic minorities. It is often argued that effects of financing reforms take a long time to materialize. This study evaluates the short-term impact of the program to determine if pro-poor financing programs can achieve immediate effects on health care utilization and out-of-pocket expenditure. Method Considering that the program is a non-random policy initiative rolled out nationally, we apply propensity score matching with both single differences and double differences to data from the Vietnam Household Living Standards Surveys 2002 (pre-program data) and 2004 (first post-program data). Results We find a small, positive impact on overall health care utilization. We find evidence of two substitution effects: from private to public providers and from primary to secondary and tertiary level care. Finally, we find a strong negative impact on out-of-pocket health expenditure. Conclusion The results indicate that the Health Care Fund for the Poor is meeting its objectives of increasing utilization and reducing out-of-pocket expenditure for the program's target population, despite numerous administrative problems resulting in delayed and only partial implementation in most provinces. The main lessons for low and middle-income countries from Vietnam's early experiences with the Health Care Fund for the Poor are that it managed to achieve positive outcomes in a short time-period, the need to ensure adequate and sustained funding for targeted programs, including marginal administrative costs, develop effective targeting mechanisms and systems for informing beneficiaries and providers about the program, respond to the increased demand for health care generated by the program, address indirect costs of health care utilization, and establish and maintain routine and systematic monitoring and evaluation mechanisms.